Dual-atria rotor modification: A comparative analysis of rotor modification and posterior wall isolation in patients with persistent and long-standing persistent atrial fibrillation - Yoshifumi Okano, PhD, MD; Hironobu Tanii, MD; Katsuya Akitsu, PhD, MD; Yamato Mifune, MD; Kosuke Takeda, MD; Yuichi Moriyama, MD; Hosei Kikushima, MD; Shintaro Yao, PhD, MD; Masaya Shinohara, PhD, MD; Hirotsugu Matsumoto, RT; Kazuhito Suzuki, PhD, MD (Heart Rhythm O2)
Background: Various methods have been devised for catheter ablation of persistent atrial fibrillation (AF). However, it remains difficult to understand the mechanism of AF and to determine the optimal method. Objective: This study aimed to evaluate the effectiveness of rotor modification (RM) compared to posterior wall isolation (PWI) in the treatment of persistent AF. Methods: The study included 50 patients in the RM group (mean age: 67.0 ± 8.7 years; 76% with long-standing persistent AF) and 50 patients in the PWI group (mean age: 66.8 ± 8.9 years; 66%). In the RM group, in addition to cryoballoon isolation of the pulmonary veins, rotors in both atria were identified using a phase mapping system and ablated at low power. In the PWI group, the pulmonary vein antrum and posterior wall were isolated together using a radiofrequency catheter. The primary end point was the maintenance of sinus rhythm, defined as freedom from atrial tachycardia, AF, and atrial flutter over a 36-month postoperative follow-up period. Results: Survival curve analysis using the log-rank test revealed a statistically significant difference (P < .001), demonstrating the superiority of RM. Conclusion: RM is suggested to be as effective as PWI or more effective in maintaining sinus rhythm in patients with persistent AF.